2013
DOI: 10.1900/rds.2013.10.171
|View full text |Cite
|
Sign up to set email alerts
|

Does Combination Therapy with Statins and Fibrates Prevent Cardiovascular Disease in Diabetic Patients with Atherogenic Mixed Dyslipidemia?

Abstract: ■ AbstractType 2 diabetes mellitus (T2DM) is associated with the development and progression of cardiovascular disease (CVD). Statins have an established efficacy in the management of dyslipidemia primarily by decreasing the levels of lowdensity lipoprotein cholesterol and thus decreasing CVD risk. They also have a favorable safety profile. Despite the statin-mediated benefit of CVD risk reduction a residual CVD risk remains, especially in T2DM patients with high triglyceride (TG) and low high-density lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 209 publications
(129 reference statements)
1
12
0
3
Order By: Relevance
“…Adverse events are also consistent with the known safety profiles of both drugs; however, fenofibric acid plus atorvastatin is associated with a higher incidence of renal impairment as compared with atorvastatin monotherapy [142]. Although fibrates in combination with statins have a highly beneficial effect on almost all lipid parameters in patients with mixed dyslipidemia, this combination does not reach the desired non-HDL-C or TG and/or HDL-C concentrations [143]. Thus, a number of larger prospective studies are eagerly anticipated to further determine the role of statin/fibrate combination in reducing the risks of atherosclerosis-related diseases.…”
Section: Therapeutic Potential Of Pparα Agonists In Atherosclerosis Asupporting
confidence: 65%
“…Adverse events are also consistent with the known safety profiles of both drugs; however, fenofibric acid plus atorvastatin is associated with a higher incidence of renal impairment as compared with atorvastatin monotherapy [142]. Although fibrates in combination with statins have a highly beneficial effect on almost all lipid parameters in patients with mixed dyslipidemia, this combination does not reach the desired non-HDL-C or TG and/or HDL-C concentrations [143]. Thus, a number of larger prospective studies are eagerly anticipated to further determine the role of statin/fibrate combination in reducing the risks of atherosclerosis-related diseases.…”
Section: Therapeutic Potential Of Pparα Agonists In Atherosclerosis Asupporting
confidence: 65%
“…Various classes of drugs have proved useful in the management of patients with type 2 diabetes (T2D) and its complications [1,[5][6][7][8][9][10][11][12]. Recent evidence demonstrated the beneficial effects of incretin-mimetic drugs in the treatment of T2D; these drugs include glucagon-like peptide-1 (GLP-1) receptor agonists and dipeptidyl peptidase 4 (DPP-4) inhibitors [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant use of statins and fibrates is believed to further increase the incidence of myalgia and muscle damage. [ 23 ] However, in our study concomitant use of fibrate with statin was found to be safe, and no increased incidence of muscle damage was reported. A meta-analysis which included six clinical trials and 1628 subjects reported no cases of myopathy or muscle damage but showed a significant increase in elevation of liver enzymes in statin-fibrate combination therapy when compared to statin monotherapy.…”
Section: Discussionmentioning
confidence: 50%
“…In such group of patients with below normal HDL-C and TG levels, addition of fibrates has been shown to provide additional benefit. [ 23 ] Other lipid parameters were also improved with use of both the drugs in the patients. Serum total cholesterol and very LDL-C levels were also reduced with use of both the drugs during the study period.…”
Section: Discussionmentioning
confidence: 98%